Activity of essential oils in vapor phase against bread spoilage fungi - Krisch, Judit (Acta Biologica Szegediensis, 2013)
The antifungal activity of marjoram and clary sage essential oils (EOs) against bread spoilage molds Aspergillus niger, Penicillium chrysogenum and Rhizopus spp. was investigated by the reversed Petri dish method in malt extract medium and on wheat, wheat-rye mixed, and rye bread slices modeling an active packaging. Changes in colony size and colony growth rate were evaluated as markers for growth inhibition effect of the EOs. In vitro the most insensitive mold was Rhizopus spp. showing no significant changes after EO treatment compared to the untreated control. However, growth of all of the investigated molds was significantly reduced on EO vapor treated bread slices. To overcome problems rising from the strong aroma of EOs further experiments are needed to find the best EOs with acceptable aroma and high effectiveness to be used in combined technologies.